RESEARCH METHODOLOGY LAB ESSENTIALS - Shazaitul Azreen Rodzalan,; Nor Hazana Abdullah,; Nor Aziati Abdul Hamid, (2023)
Research Methodology: Lab Essentials is a comprehensive guide designed to walk researchers through the various stages of conducting research, both quantitative and qualitative. It provides practical lab sheets and instructions for each step of the research process, ensuring that researchers have a solid foundation to plan, execute, and report their studies effectively. This book introduces the fundamental concepts of research, distinguishing between quantitative and qualitative methodologies. It lays the groundwork for the research journey ahead. It continues with selecting a research topic that guides researchers on how to effectively search for existing literature and information relevant to their research using Mendeley software. Then, problem statement formulation helps researchers clarify and refine their research problem, setting the stage for focused inquiry. This book also comprises of labs on LR Matrix aids in the development of a literature review matrix to synthesize existing research and formulate focused research questions and conceptualize and operationalize the variables. It also covers labs on designing the study for survey and interview and collecting data. After obtaining the data, this book includes labs regarding analyzing and interpreting quantitative and qualitative data. Lastly, reporting style offers guidance on how to effectively communicate research findings, including the structure and styleof research reports.